If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 + -2(x + 7) = 25 Reorder the terms: 11 + -2(7 + x) = 25 11 + (7 * -2 + x * -2) = 25 11 + (-14 + -2x) = 25 Combine like terms: 11 + -14 = -3 -3 + -2x = 25 Solving -3 + -2x = 25 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -2x = 25 + 3 Combine like terms: -3 + 3 = 0 0 + -2x = 25 + 3 -2x = 25 + 3 Combine like terms: 25 + 3 = 28 -2x = 28 Divide each side by '-2'. x = -14 Simplifying x = -14
| -15p=-75 | | 3x+4x-5x+3=x+3x | | 10y-5(3y+1)=8(y-4) | | Fx=(x+6)(x+5) | | 6y=13y+42 | | 2(x+7)+9=x | | 0=8a | | 4(x+3)=-36 | | (-7/12)(-4/21) | | -6k+5-7k-3= | | -9=30-2y | | 21n+28=21n-16 | | 3(4w+8)=2(6w+12) | | -8r=2r^2+7 | | 11-1/2x=-13 | | 17p+10+53q+13p-2q= | | 3/2x=1/15 | | Y=-0.002x^2+.14x+3.6 | | 45+79+68=75 | | 1/8m-1=2 | | -8-2q+4q+9= | | 5x-2x+5=8+9 | | 3/5b-9=2 | | 4a-8/16 | | 7g-9-2g= | | 4x-2x+5+6=6x-2x+3 | | 7g-8-2g= | | -9-(-19)=x/6 | | -84=-4(3p-3) | | F(x)=(x-1)(x+9) | | n/-2=3 | | -18=3(x-7) |